Comparative analysis of buckling load of circular and corrugated tubes by utilizing key performance indicators - Ur Rahim, Mohd Reyaz; Akhtar, Shagil; Bharti, Pritisha (Zielona Góra: Uniwersytet Zielonogórski)
The performance of buckling load of tubular structures under quasi-static axial loading is quite appreciable, numerous tubes of various cross-section have been extensively investigated and corrugated sections have been designed to further improve the performance. In this paper, a carefully designed set of key performance indicators (KPIs) is utilized to assess and compare the buckling load of circular and corrugated tubes.
Keywords: buckling load; tubular structures; quasi-static; key performance indicators (KPIs); circular and corrugated sections